Investigating Young Male and Female Road Users’ Behaviour as Pedestrians and Drivers - İbrahim Öztürk; Bahar Öz (Psikoloji Çalışmaları)
Young road users constitute one of the most vulnerable groups in terms of experiencing road traffic accidents as either drivers or pedestrians. Pedestrian and driver behaviours are important predictors of the road users’ safety. The present study mainly aims to investigate the relationship between behaviours of young male and female road users as drivers and pedestrians. A total number of 573 young road users (316 male, 257 female) aged from 19 to 28 (M = 22.2, SD = 1.77) participated in the present study. Participants were requested to fill out a questionnaire package including demographic information form as well as the Pedestrian Behaviour Scale (PBS), the Driver Behaviour Questionnaire (DBQ) and the Positive Driver Behaviours Scale (PDBS). In line with the aims of the present study, first, the factor structure of the Pedestrian Behaviour Scale was investigated. Following that, gender differences in pedestrian and driver behaviours were examined. In terms of gender difference, males showed more pedestrian transgressions, pedestrian aggressive violations, driver aggressive violations, driver ordinary violations and fewer driver lapses compared to females. Moreover, aberrant pedestrian behaviours were positively related to aberrant driver behaviour, whereas positive pedestrian behaviours were negatively associated with aberrant driver behaviour. While pedestrian lapses and aggressive violations were negatively related to positive driver behaviours, pedestrian transgression and positive pedestrian behaviours were positively associated with positive driver behaviours. Overall, the results indicated that young road users who expressed more aberrant pedestrian behaviours also showed more aberrant driver behaviours. The results were discussed in relation to the administration of countermeasures against aberrant driver behaviours. Considering the consistency between displayed pedestrian and driver behaviours evidenced in the present study; focusing on different road user roles in detail was shown to be important especially for planning intervention programs for specific traffic conditions or driver behaviours. Additionally, investigating different roles that young road users have provides the literature with additional knowledge which could be reflected in field administrations in the complex and dynamic nature of the traffic environment.